Efficacy of a novel ultra-sharp dilation device for dilating bare metal stent mesh in patients with hilar malignant biliary obstruction. (4th March 2021) - Kato, Shin; Kuwatani, Masaki; Kawakubo, Kazumichi; Furukawa, Ryutaro; Hirata, Koji; Takishin, Yunosuke; Hirata, Hajime; Sakamoto, Naoya
Abstract: The placement of additional stents in patients with hilar malignant biliary obstruction can be challenging when a metal stent already exists because occasionally, the catheter and delivery system of the additional stent cannot pass through the mesh of the formerly placed stent. We studied ten consecutive patients with hilar malignant biliary obstruction who underwent mesh dilation using a novel ultra-sharp dilation device (ES dilator) to assess the efficacy and safety of the ES dilator for mesh dilation. Mesh dilation using the ES dilator was successful in eight patients (8/10; 80.0%), which was the same rate as that of patients with pre-dilation using a Soehendra biliary dilation catheter (4/5, 80.0%) and patients without pre-dilation (4/5, 80.0%). In the two patients with dilation failure, the angle of the hilar bile duct branch was too steep to permit the passage of a stiff dilation device. Nonetheless, stent placement was uncomplicated in all mesh-dilated patients (8/8, 100.0%), and no adverse events related to the ES dilator were observed. The efficacy of an ultra-sharp dilation device appears promising for metallic stent mesh dilation, especially in patients where conventional methods are unsuccessful. However, additional data are necessary to confirm our findings.